Numb Chin Syndrome Leading to a Diagnosis of Salivary Ductal Adenocarcinoma: A Case Report and Review of the Literature - Wu, Lei; Zheng, Yifan; Zhou, Zhou; Liu, Yanmei; Zhang, Weixi; Wu, Qi (Frontiers in Neurology, 2017)
Numb chin syndrome (NCS) refers to a rare sensory neuropathy characterized by numbness of the chin within the distribution of the mental or inferior alveolar nerve. Though NCS is usually caused by a benign process, it should not be underestimated and a thorough diagnostic evaluation for a new or known progressive malignancy should always be performed. Here we report a case of salivary ductal adenocarcinoma that mimicked a pulpitis and periodontitis in its early presentation accompanied by numbness of chin. The course and diagnosis of this case are discussed and a brief review of the literature is presented. It is hoped for clinicians to keep the malignant possibility of NCS in mind and take a thorough examination.